Clinical Applications of Liquid Biopsy in Hepatocellular Carcinoma - Yang, Jin-Cui; Hu, Jun-Jie; Li, Yi-Xin; Luo, Wei; Liu, Jin-Zhou; Ye, Da-Wei (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is a common malignant tumor with high mortality and poor prognosis in the world. The low rate of early diagnosis, as well as the high risk of postoperative metastasis and recurrence, led to the poor clinical prognosis of HCC patients. Currently, it mainly depends on serum markers, imaging examination, and tissue biopsy to diagnose and determine the recurrence and metastasis of HCC after treatments. Nevertheless, the accuracy and sensitivity of serum markers and imaging for early HCC diagnosis are suboptimal. Tissue biopsy, containing limited tissue samples, is insufficient to reveal comprehensive tumor biology information and is inappropriate to monitor dynamic tumor progression due to its invasiveness. Thus, low invasive diagnostic methods and novel biomarkers with high sensitivity and reliability must be found to improve HCC detection and prediction. As a non-invasive, dynamic, and repeatable detection method, “liquid biopsy”, has attracted much attention to early diagnosis and monitoring of treatment response, which promotes the progress of precision medicine. This review summarizes the clinical applications of liquid biopsy in HCC, including circulating tumor cells (CTCs), circulating tumor DNA (ctDNA), and exosome in early diagnosis, prognostic evaluation, disease monitoring, and guiding personalized treatment.